2018
DOI: 10.18203/issn.2455-4529.intjresdermatol20183161
|View full text |Cite
|
Sign up to set email alerts
|

A study of skin manifestations in patients with psychiatric disorders

Abstract: <p class="abstract"><strong>Background:</strong> The interaction between psychological factors and skin diseases has long been hypothesized. Considerations of psychiatry and psychosocial factors are important for better management of dermatological disorders as coexistence of psychiatric and dermatological disorders are mostly seen. The aim of the study was to identify skin manifestations in individuals suffering from psychiatric disorders.</p><p class="abstract"><strong>Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 4 publications
1
2
1
Order By: Relevance
“…As pruritus causes scratching, it in turn stimulates the synthesis and release of inflammatory factors (23). There are a large number of inflammatory cells in the allergic reaction site, which promotes an inflammatory reaction and itching, thus leading to irritability, compulsion, and anxiety, forming a vicious cycle (24)(25)(26). These conclusions were consistent with our research results.…”
Section: Discussionsupporting
confidence: 92%
“…As pruritus causes scratching, it in turn stimulates the synthesis and release of inflammatory factors (23). There are a large number of inflammatory cells in the allergic reaction site, which promotes an inflammatory reaction and itching, thus leading to irritability, compulsion, and anxiety, forming a vicious cycle (24)(25)(26). These conclusions were consistent with our research results.…”
Section: Discussionsupporting
confidence: 92%
“…8 Samanthula and Kodali et al found that 60.4% had acne for more than 1 year duration while in our study it was 60% in patients with duration 6 months to 1 year. 9 The largest clustering of cases was identified in the same study between the ages of 15-20 years, whereas clustering was seen in our study between the ages of 20-30 years.…”
Section: Resultscontrasting
confidence: 72%
“…Reduced mood levels, poor self-esteem, neurotic symptoms or depression are not uncommon in patients with skin diseases. Among people with dermatoses, these disorders are observed much more frequently than among the general population [7][8][9][10]. The relationship between the nervous system and the skin is due to the fact that both structures originate from the same primordial embryonic structure, namely the ectoderm.…”
Section: Stress and Skin Diseasesmentioning
confidence: 99%